Analytical Study to Calculate the Seismic Forces Modification Coefficient R for the Existing RC Dual Structural Systems - ناصر عصام; حويجة بسام; ابو بالا ريهام (Latakia University Journal -Engineering Sciences Series, 2020)
The importance of adopting seismic forces modification coefficient R in the seismic analysis and design process comes from its inclusion in the ductility of the structural systems resulting from the elastic-plastic behavior of the building material, and the inherent increased resistance of its elements whose design is made at lower resistance values ​​than it, thereby reducing the base shear due to seismic motion . The majority of the researches that studied the R coefficient found their values ​​according to a NLSA, and the results showed that there are differences in the values ​​of the R factor from what was stated in the different codes for different types of structural systems, and this researches used virtual building models of the study that serve ease of access for the purpose of the research, the goal is often to study the value of the parameter R by changing one of the factors involved in its calculation. In this study, the values ​​of the R behavior coefficient of the concrete buildings were determined based on the seismic resistance of the dual structural systems with the relationship between the stiffness of the frame columns to the stiffness of the shear walls of these systems in the studied direction, using NLSA ( non-linear static analysis), and the results were compared with the values ​​of the given parameter R In the simplified tables of the Syrian Arab code and its annex 2 to year 2013, In our study, we found that there is a great difference between the resulting values ​​of the R coefficient and the values ​​given in the Syrian Arab code, in addition to increasing its values ​​by increasing both the fundamental period and the ratio of the stiffness of the frame columns to the stiffness of the shear walls of these systems.